Shelf Life of Enrobed Chicken Bites Treated with Guava Extract - Madelwar, K.; Ambadkar, R.K.; Banerjee, R.; Rathod , K.S.; Pachpor, V.R. (Journal of Meat Science, 2016)
The present study was conducted to evaluate the shelf life of enrobed chicken bites (ECB) with guava fruit extract at refrigerated storage (4±10C). White Guava Extract (WGE-1%), Red Guava Extract (RGE- 1%) and BHA (100 mg/kg) were incorporated in batter mix used for enrobing chicken bites. The products were aerobically packaged in low density polyethylene (LDPE) pouches and analyzed at an interval of 5 days during refrigerated storage (4±10C). The storage period brought about significant changes in pH, TBA values, psychrophilic count (PC) and total plate count (TPC) which showed linear increasing trend from 0 to 15th day of refrigerated storage in treated as well as controlproducts. TPC and PCwere in acceptable limits for control, BHA, RGE and WGE treated products, respectively.The sensory scores of treated and control samples for appearance, flavour, texture, juiciness and overall acceptability showed a progressive decline with increase in storage period but the scores were rated above good.
Keywords: Enrobing; Chicken bites; Guava extract; Shelf life